Effect of Different DMSO Concentrations on Expression Level of Stemness Genes in Mice Fetal Liver Stem Cells Prior to and after Cryopreservation - Borisov, Petr A.; Dimitrov, Aleksey Yu.; Ostankov, Maksim V.; Goltsev, Anatoliy N. (Problems of Cryobiology and Cryomedicine, 2014)
N/A Probl Cryobiol Cryomed 2014; 24(2):185.